2022
DOI: 10.4103/jispcd.jispcd_222_21
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anti-inflammatory Effects of α-Mangostin Soluble Film

Abstract: A BSTRACT Objectives: Plant-derived compounds are a major source of medicinal agents. Common oral diseases, including dental caries, periodontal disease, and candidiasis, are caused by biofilms. The nature of biofilm formations is complex, emphasizing the importance of finding novel products that possess bioactivity against microbes associated with those oral infections. The aims of this study were to determine the antimicrobial activity and antibiofilm formation of α-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…47 Mangosteen pericarp extract has demonstrated promise as a plaque inhibitor in mouthwashes, 48,49 and a soluble film of xanthone α-mangostin exhibited antimicrobial activity against oral pathogens and inhibited biofilm formation in vitro. 13,42 Once the effectiveness of MGTN as an antiseptic either in solution or in formulation was confirmed, we also evaluated its safety through biocompatibility assessment, confirming the lack of cytotoxicity on the 2D culture in vitro model of human gingival fibroblasts by the low LDH activity levels and improved metabolic activity induced by MGTN treatment. To go further, commercial 3D models of human epidermis and oral mucosa epithelium were used to test different gels.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…47 Mangosteen pericarp extract has demonstrated promise as a plaque inhibitor in mouthwashes, 48,49 and a soluble film of xanthone α-mangostin exhibited antimicrobial activity against oral pathogens and inhibited biofilm formation in vitro. 13,42 Once the effectiveness of MGTN as an antiseptic either in solution or in formulation was confirmed, we also evaluated its safety through biocompatibility assessment, confirming the lack of cytotoxicity on the 2D culture in vitro model of human gingival fibroblasts by the low LDH activity levels and improved metabolic activity induced by MGTN treatment. To go further, commercial 3D models of human epidermis and oral mucosa epithelium were used to test different gels.…”
Section: Discussionmentioning
confidence: 91%
“…mutans biofilm and inhibit glucosyltransferase enzyme activity, which results in the inhibition of biofilm growth . Mangosteen pericarp extract has demonstrated promise as a plaque inhibitor in mouthwashes, , and a soluble film of xanthone α-mangostin exhibited antimicrobial activity against oral pathogens and inhibited biofilm formation in vitro . , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding showed that EGCG inhibits the process of alveolar bone damage through RANKL, 10 TNF-α, 11 and increases osteoprotegerin (OPG), 10 RANK, 10,11 and IL-10. 11,12 The effect is similar to α-mangosteen, which is able to stimulate some growth factors like tumor growth factor-β, 13 and TRAP5b 14 and also inhibit the growth of etiological bacteria 15,16 and RUNX2. 14 Periodontitis is a disease of the periodontal tissues that is characterized by damage to the ligaments and surrounding alveolar bone.…”
Section: Introductionmentioning
confidence: 95%
“…α-Mangostin (α-MG), a major xanthone derivative compound isolated from the Mangosteen pericarp extract, disrupts the development of S. mutans biofilm [12]. Furthermore, Tangsuksan et al [13] reported that a soluble mucoadhesive film containing α-MG is effective against S. mutans, P. gingivalis, and C. albicans without significant cytotoxicity in vitro. The film also demonstrated anti-inflammatory activity by inhibiting nitric oxide production in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%